Air and bone-conducted vestibular evoked myogenic potentials in children with large vestibular aqueduct syndrome. (2nd January 2021) - Liu, Xuhui; Ren, Lili; Li, Jianan; Ji, Fei; Liu, Xingjian; Du, Yi; Guo, Weiwei; Wu, Ziming; Yang, Shiming
Abstract: Background: There are few studies focused on vestibular symptoms and function of the children with LVAS. Objectives: This study aimed to find the characteristics of air and bone-conducted VEMPs among children with LVAS, and to investigate the relationship between VEMPs and vestibular symptoms. Material and methods: A total of 44 children with LVAS and 10 healthy children were recruited as the case group and control group. Air and bone-conducted VEMP were performed to the participants. Results: For air-conducted measurement, there was elevated amplitude of cVEMP in case group than control group. There was no significant difference at oVEMP parameters between the case group and control group. For bone-conducted measurement, significantly longer P1 latency and shorter P1-N1 latency of cVEMP were observed among the case group; there were a series of changes in oVEMP parameters among the case group. Logistic regression model revealed that air-conducted oVEMP asymmetric ratio was valuable to predict vestibular symptoms' development among the kids with LVAS. Conclusion: Asymmetric ratio of oVEMP could be used as one predictor of developing vestibular symptoms of the children with LVAS. Applying bone-conducted VEMP as one alternative parameter of vestibular syndrome is novel and will certainly remain an area of continued investigation.